Integrated Model To Analyze FDI Role In Success of Commercialization of High-Tech Innovations in Asia - Sarli Rahman; Andi Oh; Yusrizal (Yayasan Riset dan Pengembangan Intelektual, 2020)
This study aims to analyze the role of FDI in the success of commercialization high tech innovation in Asia countries. The success was marked by the increasing contribution from Asia countries to the export value of high tech products in the world. From 49 sovereign countries in Asia, 21 countries have been selected as research samples. The result SEM analysis shows that FDI inflows to Asia countries generally pure investment from multinational companies to gain profits from the low cost of production factor in Asia, therefore increase their profit margin. In other words, FDI in Asia countries only increase production quantity of high tech products without increasing innovation activity in the countries, which innovation activity can be measured by R&D expenditure, number of resident patent application and number of scientific journals international publication.